Analysis of the influence of motivation and work environment on employee productivity - Ambarita, Rentina; Hasugian, Ruth Saulina Hasugian (Yayasan Cinta Negara Indonesia, 2025)
This study analyzes the influence of motivation and work environment on employee productivity, aiming to provide empirical evidence on how these two factors contribute to optimal organizational performance. Employee productivity is a critical determinant of business competitiveness, particularly in dynamic and competitive markets. Motivation, both intrinsic and extrinsic, drives employees to perform tasks effectively, while a conducive work environment encompassing physical conditions, organizational culture, and interpersonal relationships supports consistent performance. The research employs a quantitative approach using a survey method. Data were collected from 150 employees across various departments in a medium-sized manufacturing company through structured questionnaires. Motivation was measured using indicators of intrinsic satisfaction and extrinsic rewards, while the work environment was assessed through physical comfort, workplace safety, and social interaction quality. Employee productivity was measured based on self-reported output, efficiency, and goal attainment. Multiple regression analysis was applied to test the hypotheses. The results reveal that both motivation and work environment have significant positive effects on employee productivity. Motivation demonstrates a slightly stronger influence, indicating that psychological and reward-based drivers play a key role in enhancing performance. However, the work environment also contributes meaningfully, emphasizing the importance of providing safe, comfortable, and socially supportive conditions. These findings suggest that organizations should integrate motivational strategies with workplace improvements to achieve sustainable productivity growth